2013
DOI: 10.1172/jci70395
|View full text |Cite
|
Sign up to set email alerts
|

Impaired periamygdaloid-cortex prodynorphin is characteristic of opiate addiction and depression

Abstract: Negative affect is critical for conferring vulnerability to opiate addiction as reflected by the high comorbidity of opiate abuse with major depressive disorder (MDD). Rodent models implicate amygdala prodynorphin (Pdyn) as a mediator of negative affect; however, evidence of PDYN involvement in human negative affect is limited. Here, we found reduced PDYN mRNA expression in the postmortem human amygdala nucleus of the periamygdaloid cortex (PAC) in both heroin abusers and MDD subjects. Similar to humans, rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 55 publications
4
36
1
Order By: Relevance
“…[16][17][18] Moreover, reduced PDYN expression in the human brain is associated with opiate dependency. 35,36 Interestingly, in the present study the continuous exposure condition of ELF-EMF was associated with the lower expression levels of the PDYN. It may indicate that in cells exposed to ELF-EMF the PDYN expression level significantly decreased via production of ROS.…”
Section: Discussionsupporting
confidence: 45%
“…[16][17][18] Moreover, reduced PDYN expression in the human brain is associated with opiate dependency. 35,36 Interestingly, in the present study the continuous exposure condition of ELF-EMF was associated with the lower expression levels of the PDYN. It may indicate that in cells exposed to ELF-EMF the PDYN expression level significantly decreased via production of ROS.…”
Section: Discussionsupporting
confidence: 45%
“…Two Herpes Simplex Virus (HSV) vectors were constructed for the purposes of these studies based on vectors that we and others have extensively characterized with regard to their time course and selectivity of expression (Ferguson et al, 2011, Anderson et al, 2013, Ferguson et al, 2013, Michaelides et al, 2013). HSV is an enveloped, double-stranded DNA virus that selectively enters neurons via glycoprotein interactions.…”
Section: Methodsmentioning
confidence: 99%
“…the strain is not substantially retrogradely transported) (Fink et al, 1996). The first utilizes preprodynorphin promoter (pDYN) to drive transgene expression in dMSNs while the second uses the preproenkephalin promoter (pENK) to target iMSNs; both are >90% selective (Ferguson et al, 2011, Anderson et al, 2013, Ferguson et al, 2013, Michaelides et al, 2013). To allow us to distinguish from endogenous 5-HT 6 receptors, a double hemagglutinin (2xHA) epitope-tag was introduced to the N terminal of the rat 5-HT 6 receptor gene by cloning an oligonucleotide in-frame upstream of the 5-HT 6 sequence using pBlueScript as this does not interfere with receptor functionality as shown previously (Mitchell et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson et al (Anderson et al, 2013) employed DREADDs in a novel way, which they termed DREADD-assisted metabolic mapping (DREAMM; see also (Michaelides et al, 2013)), to interrogate wider circuit activity after hM4Di DREADD inhibition of dynorphin-expressing neurons in rat periamygdaloid cortex (PAC). They found that dynorphin mRNA in PAC is higher in humans and rats with heroin self-administration history, so they measured effects of DREADD-mediated inhibition of PAC dynorphin neurons on behavior, and on wider brain activity as measured by radiolabeled glucose utilization with PET imaging.…”
Section: Section 2 – Highlights Of Dreadd Applications In Behavioral mentioning
confidence: 99%